Analysing social networks for social work practice: A case study of the Facebook fan page of an online youth outreach project. (January 2018) - Chan, Chitat
Abstract: This study adopted social network analysis (SNA) to interpret a Facebook fan page used by a youth outreach project in Hong Kong. The study aimed to: i) explore what types of open data can be captured from social media, ii) explore in what ways SNA metrics can be used to generate meaningful indicators that help track relationship changes, and iii) examine to what extent SNA findings agree with social workers' perceptions. These results preliminarily suggest the feasibility and validity of SNA in social work practice research. This study adds to the emerging knowledge base of how practitioners and researchers might use SNA to assess social networks, supplement need assessments, track service users' behavioural changes, and evaluate services. Highlights: Social network analysis (SNA) software can capture publicly available information supported by the API of social media. Betweenness Centrality, and other SNA measure can systematically show the change of network behaviours over time. Social workers and researchers can use SNA to interpret social networks, supplement need assessments, and evaluate services.